Antimicrobial gum bio-based nanocomposites and their industrial and biomedical applications. Issue 99 (28th November 2019) - Nazarzadeh Zare, Ehsan; Makvandi, Pooyan; Borzacchiello, Assunta; Tay, Franklin R.; Ashtari, Behnaz; V. T. Padil, Vinod
Abstract : Schematic illustration of the gum biobased materials in biomedical and industrial applications. Abstract : Gum polysaccharides are derived from renewable sources. They are readily available, inexpensive, non-hazardous and eco-friendly. Depending upon the source, gums may be categorized as microbial gums, plant exudate gums or seed gums. Naturally occurring gum carbohydrates find multiple applications in the biomedical arena, compared with synthetic compounds, because of their unique structures and functionalities. Gums and their biocomposites are preferred for sustained drug delivery because they are safe and edible as well as more susceptible to biodegradation. The present review provides a state-of-the-art conspectus on the industrial and biomedical applications of antimicrobial gum-based biocomposites. Different kinds of gums polysaccharides will first be addressed based on their sources. Metal-, carbon- and organic-based nanostructures that are used in gum nanocomposites will then be reviewed with respect to their industrial and biomedical applications, to provide a backdrop for future research.